2023
DOI: 10.1097/yic.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates and prognostic implications of severe suicidal ideation in major depressive disorder

Abstract: Suicidal ideation (SI) is a risk factor for suicidal behaviour. To ascertain the clinical correlates and prognostic impact of severe SI, we analysed 249 outpatients with major depressive disorder (MDD) and suicidal thoughts included in the COmbining Medications to Enhance Depression outcome (CO-MED) trial. Patients with severe SI (36%) were younger at disease onset (P = 0.0033), more severely depressed (P = 0.0029), had more lifetime suicidal behaviour (P < 0.0001) and psychiatric comorbidities (panic disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…However, the impact of underlying bipolarity on suicide risk in MDD has been extensively discussed by Rihmer and Rihmer [27]. In our previous work, childhood maltreatment and subthreshold bipolarity were associated with the intensity of SI [48]. The current analysis added a new piece to the mosaic: these variables may increase suicide risk independently of suicide ideation and may be markers of suicidality in subjects who did not report ideation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the impact of underlying bipolarity on suicide risk in MDD has been extensively discussed by Rihmer and Rihmer [27]. In our previous work, childhood maltreatment and subthreshold bipolarity were associated with the intensity of SI [48]. The current analysis added a new piece to the mosaic: these variables may increase suicide risk independently of suicide ideation and may be markers of suicidality in subjects who did not report ideation.…”
Section: Discussionmentioning
confidence: 83%
“…Cholesterol has been studied as a biomarker of suicidality for more than three decades since early reports suggested a possible association between excess mortality from violence and the use of cholesterol-lowering drugs [105]. In most studies, low total cholesterol has been associated with an increased risk of SB, including SI [44], suicide attempt [41‒43] and suicide completion [42‒108]. In a review of the literature on cholesterol lipoproteins, a meta-analysis found a negative association between LDL levels and suicide attempts in patients with MDD [109].…”
Section: Discussionmentioning
confidence: 99%
“…However the majority of studies suggest that anhedonia should be considered a relevant risk factor for possible suicidal behaviors, this is an issue considering the persistence of suicidal ideation also after treatment [ 47 - 49 ]. Higher levels of anhedonia in depression have been linked to higher suicidal ideation both in cross-sectional and longitudinal studies.…”
Section: Prognostic Valuementioning
confidence: 99%
“…Several risk factors have been proposed for the association of MDD and suicidality. These risk factors include male gender, depression severity, age of onset and course of depression, a family history of psychiatric disorders, previously attempted suicide, comorbid psychiatric disorders such as anxiety disorders, and abuse and violence during childhood [37][38][39][40]. In addition, specific symptoms of depression, such as hopelessness, self-blame, irritability, insomnia and bipolar features, have also been associated with an increased risk of suicidality in individuals with MDD [39,40].…”
Section: Major Depressive Disordersmentioning
confidence: 99%